2023
DOI: 10.1021/acssuschemeng.2c06542
|View full text |Cite
|
Sign up to set email alerts
|

Operando Electrochemical Liquid-Cell Scanning Transmission Electron Microscopy (EC-STEM) Studies of Evolving Cu Nanocatalysts for CO2 Electroreduction

Abstract: The design and synthesis of nanocatalysts with welldefined sizes, compositions, and structures have revolutionized our accessibility to tunable catalyst activity and selectivity for a variety of energy-related electrochemical reactions. Nonetheless, establishing structure-(re)activity correlations requires the understanding of the dynamic evolution of pristine nanocatalysts and the identification of their active states under operating conditions. We previously communicated the operando observation of Cu nanoca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 30 publications
0
22
0
Order By: Relevance
“…Surprisingly, a relatively high number of studies concerning Cu-based catalysts for CO 2 reduction using in situ TEM have been reported, such as. 159–161…”
Section: Deep Insights Into Pt-based Nanostructures – Advanced (S)tem...mentioning
confidence: 99%
“…Surprisingly, a relatively high number of studies concerning Cu-based catalysts for CO 2 reduction using in situ TEM have been reported, such as. 159–161…”
Section: Deep Insights Into Pt-based Nanostructures – Advanced (S)tem...mentioning
confidence: 99%
“…For example, Yang and co-workers 14 used this approach to track the structural evolution of a monolayer of 7 nm Cu nanoparticles, which were found to be highly mobile, forming metallic nanograins, the boundaries of which were determined to serve as active sites for C−C coupling. A following study by the same group 12 improved the technique by exploiting the electrogenerated H 2 bubbles to create a thin-liquid layer, improving the spatial resolution further. The authors were able to visualize the transition of the self-assembled pristine 7 nm Cu nanoparticle ensemble (Figure 1d) to the active polycrystalline Cu nanograin phase.…”
Section: Reduction Of Spatial Averagingmentioning
confidence: 99%
“…(e) False-color image showing different crystal domains on Cu nanograins at −0.8 V vs RHE obtained by operando electrochemical 4D-STEM diffraction imaging. Adapted with permission from ref . (f) Experimental (black) and DFT-calculated (purple, blue, and red) SERS spectra of Ni­(tpyS) 2 with relevant identified vibrational modes highlighted.…”
Section: Electrocatalystsmentioning
confidence: 99%
See 2 more Smart Citations